Dino-splashing - Smallman, Steve (Pearson Education China, 2010)
"Dino-Splashing" is a lively children's book that features playful dinosaur characters engaging in fun, splashy adventures. With vibrant illustrations and rhythmic text, it captures the excitement of dinosaurs playing in water, promoting themes of friendship and joy. The story is designed to entertain young readers while also encouraging imaginative play and exploration of the prehistoric world. Perfect for storytime, it invites children to dive into a colorful, dino-filled adventure!